Case overview of children’s thalassemia at RSAB Harapan Kita Jakarta - Susilowati, Rina Priastini; Pratanu, Lydia; Putri, Dyah Ayu Adella (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2024)
Thalassemia is a hereditary blood disorder characterized by reduced alpha or beta globin chain synthesis, independent of sex or age. While thalassemia minor often presents with mild or no symptoms, thalassemia major manifests with severe anemia, pallor, fatigue, decreased appetite, and recurrent infections from birth. The aim of this research is to describe the description of cases of thalassemia children at RSAB Harapan Kita. This research is a descriptive study with a cross-sectional design regarding the description of cases of thalassemia children. Study participants were pediatric patients diagnosed with thalassemia at the hospital. Inclusion criteria encompassed individuals younger than 19 years with a documented history of comorbidities. Exclusion criteria included patients with incomplete or damaged medical records and those aged 19 years or older. Medical record data that met the inclusion criteria was 48 subjects with a minimum sample size of 41 subjects. The data used in this research was processed with SPSS ver. 25 and presented in table form. The results showed that the highest proportion of thalassemia children was in the age group 6-11 years (41.7%), male sex (56.3%), the main complaint was pallor (87.5%), type of β thalassemia (83, 3%), pre-transfusion Hb level <9 g/dL (79.2%), and without other comorbidities (64.6%).